2014
DOI: 10.1111/joss.12121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipid Content on Saltiness Perception: A Psychophysical Study

Abstract: The objective of this study was to evaluate the effect of oil addition (10, 20 and 40% of oil in water) on saltiness perception as a function of NaCl concentration. A sensory panel (n = 20) was selected from the local community and trained to taste saltiness intensity using magnitude estimation. Data obtained were fitted to the Stevens’ power law. As expected, saltiness intensity increased as [NaCl] in the aqueous phase ([NaCl]aq) increased, for a constant type of sample. All types of samples (0, 10, 20 and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
(43 reference statements)
1
23
2
Order By: Relevance
“…Suzuki and others () concluded that the response toward NaCl saltiness intensity decreased as an oil phase was introduced in the system. They reported estimated n values of 0.87, 0.66, and 0.47 for 0%, 20%, and 40% oil systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Suzuki and others () concluded that the response toward NaCl saltiness intensity decreased as an oil phase was introduced in the system. They reported estimated n values of 0.87, 0.66, and 0.47 for 0%, 20%, and 40% oil systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Oil affects the taste perception by increasing the viscosity of liquid foods and affecting the diffusion coefficients and retention times of taste substances in the oral cavity (Barylko‐Pikielna and others ; Mela and others ). Therefore, sensory perception of basic tastes can be affected by various physical properties of emulsions (Dresselhuis and others ; Rietberg and others ; Suzuki and others ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They observed that the fat content in the milk primarily influences the saltiness perception. Suzuki et al (2014) hypothesized oil contributes to mouth-coating in the tongue that delays the rinsing of water phase from tongue, which may increase the saltiness. Meanwhile, Scanlon and Sanders (2007) studied that fat contributes to activate K + channels in the taste bud and thus, increases the transmitter release.…”
Section: Saltiness Perception Of Emulsion With Different Oil Concentrmentioning
confidence: 99%